Anatomy based corridors to the infratemporal fossa: Implications for endoscopic approaches. Issue 5 (27th December 2019) - Li, Lifeng; London, Nyall R.; Prevedello, Daniel M.; Carrau, Ricardo L.
Abstract: Background: The infratemporal fossa (ITF) represents an area densely packed with neurovascular structures within irregular boundaries. The goal of this study was to classify the ITF into zones corresponding to its anatomical spaces and the order in which they are encountered during an endonasal approach (anteroposterior axis). Methods: Six cadaveric specimens (12 sides) with injected colored latex were dissected. Following an endoscopic medial maxillectomy and Denker's approach, a progressive exploration of the masticator space and upper parapharyngeal space was completed. A classification of the ITF based on well‐defined spaces was ascertained. Results: The ITF was divided into five zones: Zone 1 (retromaxillary space)—space lying between the posterolateral wall of the maxillary sinus and the temporalis and pterygoid muscles. Zone 2 (superior interpterygoid space)—area including the superior head of the lateral pterygoid muscle, V3, and foramen ovale. Zone 3 (inferior interpterygoid space)—includes the inferior head of lateral pterygoid muscle, medial pterygoid, and temporalis muscles, and the space enclosed by these muscles. Zone 4 (temporo‐masseteric space)—space lateral to the temporalis muscle (comprising fat mostly). Zone 5 (tubopharyngeal space)—includes the Eustachian tube, tensor, and levator veli palatini muscles, and structures in upper parapharyngeal space. Conclusion: The ITF can be visualized as five zones based on spaces enclosed by the masticator muscles and upper parapharyngeal structures. This novel classification system is useful to guide endoscopic approaches to the ITF, while decreasing the potential for injury of neurovascular structures and pterygoid muscles.